2006
DOI: 10.1007/s11104-005-6066-y
|View full text |Cite
|
Sign up to set email alerts
|

Autotoxicity Against Germination and Seedling Emergence in Cistus ladanifer L

Abstract: Autotoxic species are those which adversely affect their own seeds' germination and/or seedling development. Cistus ladanifer L (labdanum or jara) has been shown to have a pattern of allelopathic behaviour against the herbs that share its habitat. The present work studied whether an autotoxic effect also exists. The aqueous solution obtained from washing jara leaves was found by itself to inhibit germination and cotyledon emergence of the species' seeds. When these same trials were carried out in soils, autoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 23 publications
1
46
0
1
Order By: Relevance
“…Autotoxicity is an intraspecific type of allelopathy, occurring when a plant species releases chemical substances that inhibit or delay the germination and growth of the same plant species (Alias et al 2003;Hegab & Ghareib 2009;Gomaa & AbdElgawad 2012). The autotoxicity of S. oleraceus might have implications for the biocontrol of S. oleraceus itself.…”
Section: Discussionmentioning
confidence: 99%
“…Autotoxicity is an intraspecific type of allelopathy, occurring when a plant species releases chemical substances that inhibit or delay the germination and growth of the same plant species (Alias et al 2003;Hegab & Ghareib 2009;Gomaa & AbdElgawad 2012). The autotoxicity of S. oleraceus might have implications for the biocontrol of S. oleraceus itself.…”
Section: Discussionmentioning
confidence: 99%
“…Soil sickness may be attributed to autotoxicity, soil microflora imbalance and changes in soil physiochemical properties (Young, 1984;Yu and Matsui, 1994). Previous studies report that build-up of plant pathogens is one of the major causes in soil sickness in Cistus ladanifer (Hassan et al, 1989), peach (Benizri et al, 2005), cucumber (Yao et al, 2006), Rehmannia glutinosa (Chen et al, 2007), Liriope (Zhao et al, 2010), while autotoxicity has been reported to be one of the major causes in soil sickness in cucurbit crops (Yu et al, 2000), alfalfa (Segiun et al, 2002), Cistus ladanifer (Alías et al, 2006), cucumber (Yao et al, 2006) and wheat (Wu et al, 2007). In many cases, soil microorganism played either direct or indirect role in yield reduction (Manici et al, 2003;Hu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The autoinhibition and replant problems in natural forests and managed tree plantations can result in a decrease of seedling growth or delayed germination, limiting offspring (Alias et al 2006;Fernandez et al 2008;Kong et al 2008a). The data generated in this study clearly showed that the Manchurian walnut seedlings had difficulty surviving in their own plantation and that their growth was inhibited by their own soil and root exudates.…”
Section: Discussionmentioning
confidence: 70%